2012
DOI: 10.1128/cvi.05505-11
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines Displaying Mycobacterial Proteins on Biopolyester Beads Stimulate Cellular Immunity and Induce Protection against Tuberculosis

Abstract: New improved vaccines are needed for control of both bovine and human tuberculosis. Tuberculosis protein vaccines have advantages with regard to safety and ease of manufacture, but efficacy against tuberculosis has been difficult to achieve. Protective cellular immune responses can be preferentially induced when antigens are displayed on small particles. In this study, Escherichia coli and Lactococcus lactis were engineered to produce spherical polyhydroxybutyrate (PHB) inclusions which displayed a fusion prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 54 publications
1
71
0
Order By: Relevance
“…5). Parlane et al also demonstrated the induction of a protective response in mice vaccinated with similar polyester particles expressing antigens Ag85A-ESAT6 which was superior to that induced by soluble antigens (62). The versatility and potential of the bead antigen delivery system in eliciting different complementary facets of the immune response could be applied to the development of multivalent vaccines (52).…”
Section: Discussionmentioning
confidence: 99%
“…5). Parlane et al also demonstrated the induction of a protective response in mice vaccinated with similar polyester particles expressing antigens Ag85A-ESAT6 which was superior to that induced by soluble antigens (62). The versatility and potential of the bead antigen delivery system in eliciting different complementary facets of the immune response could be applied to the development of multivalent vaccines (52).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of Rv3615c to the reagent containing ESAT6 and CFP10 significantly improves the sensitivity of skin tests in the naturally infected cattle and does not cause responses in vaccinated or healthy cattle (3), indicating that the use of a protein cocktail of CFP10, ESAT6, and Rv3615c would be beneficial for TB skin testing. Furthermore, antigens from pathogenic mycobacteria, such as antigen 85A and ESAT6, had been shown to stimulate stronger cellular immune responses when they were displayed on the surface of polyester beads than when they were free antigens (24). Accordingly, CFP10-Rv3615c-ESAT6 immobilized on the surface of a polyester bead might act as a more sensitive and cost-effectively producible diagnostic reagent than the respective free antigens.…”
Section: Discussionmentioning
confidence: 99%
“…These polyester beads showed immunogenicity in vivo leading to specific Th1 and Th2 immune responses (14,23,24). The aim of this study was to genetically engineer E. coli to produce fusion proteins which mediate formation of polyester beads displaying selected TB antigens (CFP10, ESAT6, and Rv3615c) suitable for TB skin test applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreign proteins have been displayed on the polyester beads by translationally fusing them to a polyester synthase (PhaC), which has mediated formation of protein-displaying beads in recombinant E. coli (15,16). The beads are 100 to 500 nm in diameter, and beads contain an amorphous hydrophobic polyester core surrounded by proteins, including the fusion protein composed of PhaC and foreign proteins (12,17). Interestingly, immunological studies using antigen-displaying beads revealed that the beads showed adjuvant properties by enhancing the immune response to the displayed antigen, compared to its soluble counterpart (18).…”
mentioning
confidence: 99%